The Role of The Guidance and Counseling Teacher in Improving Student’s Argumentation Ability at MTS Mal UIN North Sumatra Medan - Abdurrahman Abdurrahman (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to describe the role of BK teachers in improving students' ability to argue at MTs MAL UIN North Sumatra Medan. The research method used is a qualitative approach. The research subjects were BK teachers, students of MTs MAL UIN North Sumatra Medan, subject teachers taken by snowball sampling. Interview data collection techniques, observation and documentation. Data analysis technique is done by editing, classifying, reducing and presenting data. The results showed that: 1) The argumentation ability of class VII students of MTs MAL UIN North Sumatra Medan can now be said to be even better, in the sense that students dare to argue and do not show shy behavior when arguing. 2) The form of the guidance and counseling teacher's role in improving students' argumentation skills through the implementation of information services, group guidance and content mastery and collaborating with subject teachers and homeroom teachers. there is a special time allocated to carry out guidance and counseling. Meanwhile, the BK teacher's efforts in overcoming these obstacles are by continuing to provide guidance and direction to students so that they are still willing to follow the implementation of guidance and counseling services and make closeness that touches students' socio-emotional. BK teachers also take advantage of the empty lesson hours because the teacher is not present to provide counseling services.